Keragaman Daerah Kontrol DNA Mitokondria Rusa Timor (Cervus timorensis timorensis) di Pulau Timor, Alor, dan Pantar - Zein, M. Syamsul (Universitas Atma Jaya Yogyakarta, 2007)
A study on mtDNA control region diversity of the timor deer was conducted in EastNusa Tenggara Province. Sample consisted of 20 individuals from 3 islands (Timor,Pantar, and Alor). Total DNA were extracted from leucocyte (buffy coat). Fragmentcontrol region of the mitochondrial DNA were amplified by Polymerase ChainReaction (PCR) using primers of forward primer5â€AAACCAGAAAAGGAGAGCAAC3â€ and reverse primer5â€TCATCTAGGCATTTTCAGTGCC3â€. Nucleotide sequence of the mitochondrialcontrol region were aligned by using ClastalX and phylogenetic analyses by Neighbor-Joining methode. Kimura two-parameter model of nucleotide substitution usingpairwise distance calculation program was implemented with the Mega softwareversion 3. The purposes of this study, were to examine the control region (D-Loop) ofthe mitochondrial DNA and to discuss the phylogeography of the Cervus timorensistimorensis in East Nusa Tenggara Province. Results indicated that from 435 basenucleotide sequences, 16 polymorphic sites with 8 haplotypes were found among 3islands. Haplotype diversity and nucleotide diversity were 0.056 and 0.039. DNAdistances values ranged from 0.014 to 0.021.